The grammatical codiﬁcation of self-movement in cyberspace: A phenomenological-cognitivist study - Unternbäumen, Enrique Huelva (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The aim of this paper is to explain why we utilize a grammar typical of movement when referring to activities conducted in cyberspace. We argue that to a large degree, perception of our activities in cyberspace has recourse to the same image schemas inherent to the concept of self- movement in physical space. This sharing of image schemas unleashes a complex process of conceptual integration, which results in the construction of a concept of self-movement proper to cyberspace. We argue on behalf of perceptual (rather than an ontological) underpinnings of grammar, in the sense that it codiﬁes image schemas inherent to our perceptions. We concretely demonstrate that thematic roles correspond to salient aspects of the image schematic structure underlying our perception of self-movement in cyberspace. Finally, we postulate that the process of grammatical codiﬁcation is regulated by the principle of perceptual prominence.